Heat Stress Impacts Immune Status in Cows Across the Life Cycle - Dahl, Geoffrey E.; Tao, Sha; Laporta, Jimena (Frontiers in Veterinary Science, 2020)
Heat stress has myriad effects on dairy cattle across the life cycle. Whereas the most commonly recognized impacts are associated with production responses, emerging evidence indicates that heat stress profoundly alters the immune response of calves and cows, from the prenatal stage through lactation. For example, in utero heat stress reduces passive immune transfer regardless of colostrum source, relative to normothermic conditions in late gestation. Dry cows exposed to heat stress have lower immunoglobulin responses to ovalbumin vaccination, but this effect dissipates with cooling following parturition. Conversely, cows under heat stress when dry exhibit carryover effects on the innate arm of the immune system in early lactation. In this paper we review the effects of heat stress throughout the life cycle of the dairy cow, with particular emphasis on the impact of heat stress during late gestation on the cow and the developing fetus, both before and after parturition. In addition, the impact of altered immune status under heat stress on other physiological systems, especially those supporting milk production, are considered. Finally, management interventions to prevent and reverse the effect of heat stress are presented.